Effects of language proficiency and learning styles on the acquisition of conditions and violations of it-cleft constructions - Zaidi, Shafqat; Yasmeen, Fariha; Nimehchisalem, Vahid; Mohd Kasim, Zalina; Mohamad Ali, Afida (Scientific Research Publishing, 2024)
This paper studies the effects of language proficiency and learning styles on the acquisition of conditions and violations of it-cleft constructions. Pakistani ESL learners encounter difficulties in constructing grammatically accurate conditions sentences and in avoiding violations of it-cleft constructions. Hence, the study examines the conditions and violations of it-cleft constructions in relation to L2 proficiency and learning styles. This study seeks to answer the main research question: “How well do Pakistani ESL learners with varying degrees of second language proficiency and learning styles accurately identify conditions and violations of it-cleft constructions?” The study utilized a quantitative approach. A sample of three hundred and ninety participants with varying degrees of L2 proficiency and learning styles was selected from certain universities in Lahore, Pakistan. The study applied a stratified random sampling technique to draw the required sample size. The participants were additionally categorized into elementary, intermediate, and advanced levels of L2 proficiency. Each L2 proficiency included 130 respondents. The Grammaticality Judgment Task (GJT) was administered to assess participants’ grammatical understanding of the conditions and violations of it-cleft constructions. A bivariate analysis of variance (MANOVA) was used to investigate a significant variation in the mean scores of the GJT across different levels of second language proficiency and learning styles. The results indicated a notable variation in average scores in GJT among different L2 proficiency groups and also between learners who are field-dependent and those who are field-independent. The findings also indicated a substantial main and interaction effect of language proficiency and learning styles on GJT. FI learners scored better than FD learners on conditions and violations of it-cleft constructs. The results reflect intriguing educational ramifications. ELT educators and curriculum developers would create instructional exercises focused on cleft constructions specifically tailored for learners with limited language proficiency.